2022
DOI: 10.3390/ijms23105732
|View full text |Cite
|
Sign up to set email alerts
|

Salinity Tolerance of Halophytic Grass Puccinellia nuttalliana Is Associated with Enhancement of Aquaporin-Mediated Water Transport by Sodium

Abstract: In salt-sensitive plants, root hydraulic conductivity is severely inhibited by NaCl, rapidly leading to the loss of water balance. However, halophytic plants appear to effectively control plant water flow under salinity conditions. In this study, we tested the hypothesis that Na+ is the principal salt factor responsible for the enhancement of aquaporin-mediated water transport in the roots of halophytic grasses, and this enhancement plays a significant role in the maintenance of water balance, gas exchange, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 91 publications
2
12
0
Order By: Relevance
“…We also demonstrated that NaCl treatments enhanced cell hydraulic conductivity (L pc ) in roots of Puccinellia nuttallianna and had relatively little effect on L pc in Poa juncifolia while, similarly to other glycophytes (Lee & Zwiazek, 2015;Carmen martínez-Ballesta et al, 2003), NaCl had a strong inhibitory effect on L pc in Poa pratensis (Vaziriyeganeh et al, 2018(Vaziriyeganeh et al, , 2022. Since in our earlier study (Vaziriyeganeh at al. 2022), we also determined that Puccinellia nuttalliana treated with 150 mM NaCl maintained leaf water potentials at the control level when measured after 6 days of treatment, we used this treatment duration to investigate the effects of NaCl on aquaporin expression in the present study.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…We also demonstrated that NaCl treatments enhanced cell hydraulic conductivity (L pc ) in roots of Puccinellia nuttallianna and had relatively little effect on L pc in Poa juncifolia while, similarly to other glycophytes (Lee & Zwiazek, 2015;Carmen martínez-Ballesta et al, 2003), NaCl had a strong inhibitory effect on L pc in Poa pratensis (Vaziriyeganeh et al, 2018(Vaziriyeganeh et al, , 2022. Since in our earlier study (Vaziriyeganeh at al. 2022), we also determined that Puccinellia nuttalliana treated with 150 mM NaCl maintained leaf water potentials at the control level when measured after 6 days of treatment, we used this treatment duration to investigate the effects of NaCl on aquaporin expression in the present study.…”
Section: Discussionsupporting
confidence: 60%
“…However, L pc in roots of Arabidopsis plants overexpressing AtPIP2;5 was unaffected by the NaCl treatments, which caused several‐fold L pc reductions in the wild‐type plants (Lee & Zwiazek, 2015). The increased expression of PIP2;2 in Puccinellia nuttalliana and Poa juncifolia is likely linked to the enhanced water transport by NaCl (Vaziriyeganeh et al, 2018, 2022). The increase in PIP2;2 transcript levels in NaCl‐treated Puccinellia nuttalliana was also earlier confirmed by transcriptome analysis (Vaziriyeganeh et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6). It was demonstrated the significant differences among Puccinellia species for chlorophyll a, b and a:b ratio and the supremacy of the P. pratensis [30]. Similarly, genotype X had a high performance for leaf thickness in all sowing times (Figs.…”
Section: Resultsmentioning
confidence: 85%